PEMBELAJARAN MENCERITAKAN KEMBALI ISI TEKS CERITA RAKYAT SECARA TERTULIS DENGAN MENGGUNAKAN MODEL INKUIRI PADA PESERTA DIDIK KELAS VII SMP NEGERI 1 PLERED - Igar Siti Nurkholisoh; R. Panca Pertiwi Hidayati; Desti Fatin Fauziyyah (STKIP Subang, 2023)
This research is motivated by the ability to retell the contents of the story text. Because the learning model did not vary, students' interest decreased, this study focused on the ability to retell the contents of the story text with stages or processes. Therefore, the writer uses the inquiry model to teach retelling of the contents of the story in writing. The purpose of this study was to determine the ability of the writer to plan, implement and evaluate learning to retell the contents of the story; knowing the ability of students in learning to retell the contents of folklore texts in writing through the inquiry model; knowing the effectiveness of the inquiry model in learning to retell the contents of folklore texts in writing; determine the ability of students to learn between the experimental class using the inquiry model and the control class using the lecture method to retell the contents of folklore texts in writing. This study used a quantitative experiment with a quasi design,